Tipe Kepribadian Tokoh Utama dalam Cerpen al-Dunya> Riwa>yah Karya Tawfi>q al-Haki>m: Kajian Psikologi Sastra Carl Gustav Jung - Noriska, Zacky Aqsha; Chalis, Nur (Universitas Negeri Jakarta, 2025)
This study aims to analyze the personality types of the main character in the short story al-Dunyā Riwāyah by Tawfīq al-Ḥakīm. The research is based on the view that personality in literary works represents the psychological aspects of characters, which can deepen the understanding of the plot and conflict. The method used is descriptive qualitative with a psychology of literature approach, applying Carl Gustav Jung’s theory of personality. Data collection techniques include reading, note-taking, and translation, while data analysis is conducted narratively through the stages of identification, classification, and psychological interpretation of the main character. The results show that the main character in this short story represents eight personality types according to Jung: introvert-thinking, introvert-feeling, introvert-sensing, introvert-intuition, extrovert-thinking, extrovert-feeling, extrovert-sensing, and extrovert-intuition. These findings reveal the character’s psychological complexity and may serve as a reference for future research exploring Arabic literature through a psychology of literature lens, particularly using Jung’s theory.